Effect of water erosion on flame retardancy of high‐impact polystyrene/magnesium hydroxide composite and its mode of action. (15th December 2019) - Liu, Jichun; Li, Hang; Chang, Haibo; He, Yunpeng; Zhong, Anyang; Wu, Sai; Pan, Bingli
Summary: High‐impact polystyrene (HIPS) flame retarded by magnesium hydroxide (MH) was treated in water at different conditions. The effect of water erosion on flame retardancy of the HIPS/MH composite and its mode of action was investigated by various means. The results indicate that both limiting oxygen index value and UL‐94 rating of the HIPS/MH composite decrease observably after water erosion. The average heat release rate, average mass loss rate, total heat release, and total smoke release of the composite all increase remarkably after water erosion. The MH content in the surface layer of the HIPS/MH composite reduces, and the surface of this composite becomes rough and porous after erosion. The water‐eroded composite shows a loose and discrete surface morphology after subjected to fire, which favors heat transfer and mass exchange between flame area and the underlying polymers. Consequently, both flame retardancy and smoke suppression of the polymer composite decrease significantly. The decrease in flame retardancy occurs in condensed phase. The result of this work has provided a basis for further investigations to prevent this detrimental effect induced by water erosion.